THE IMPACT OF GROWTH MINDSET AND INTRINSIC MOTIVATION ON SELF-REGULATED LEARNING: A STUDY OF MAHASANTRI AT MA'HAD AL-JAMI'AH - Tarsono, Tarsono; Rachman, Dicky Alfian Nur; Mafaizah, Sheila; Ahmad Akbar, Paisal; Haq, Rijalul; Haedarullah, Haedarullah; Syahruramadhan, Syahruramadhan (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
Self-Regulated Learning (SRL) is crucial aspect for Mahasantri at Ma'had Al-Jami'ah who manage dual academic workloads. Preliminary findings indicate suboptimal SRL levels, evicended by low initiative in congregational prayers and a reliance on external supervision. This study emipirically analyzes the simultaneous impact of growth mindset and intrinsic motivation on SRL theoretically the primary psychological drivers of learning independence. Employing a quantitative correlational method with 51 respondents through incidental sampling, data were analyzed using Spearman's rho, Pearson correlation tests, and multiple linear regression analysis, following rigorous validity and reliability testing (Alpha Cronbach 0.933). Result demonstrate that both variables had a significant and strong positive relationship with SRL (Growth Mindset: r = 0.681; Intrinsic Motivation: r = 0.803). Simultaneously, growth mindset and intrinsic motivation contributed 67.6% to the variation in SRL of students (F = 49.976, p < 0.05), with intrinsic motivation being the most dominant predictor (B = 0.527). This finding provides implications for the urgency of strengthening the growth mindset and intrinsic motivation in the design of student development at Ma'had Al-Jami'ah on the basis of self-regulated learning. These finding highlight the urgency of fostering a growth mindset and internalizing motivation within mahasantri development programs to enhance effective self-regulated learning.